(untitled) (Bangladesh Rice Journal, 2018)
Attempts have been made in this paper to overview the existing cropping patterns, crops diversity and cropping intensity in Rajshahi region. The study was conducted in all the upazilas of four districts of Rajshahi region during 2014-15 using pre-tested semi-structured questionnaires. The most predominating crop in this area was rice where exclusive rice based patterns occupied 40.48% of NCA. Boro-Fallow-T. Aman was the dominant cropping pattern, occupied 22.83% of NCA in 27 upazilas out of 32. The second dominant cropping pattern in Rajshahi region was Boro-Fallow-Fallow. It occupied 7.23% of NCA of the region and existed in 28 upazilas. Wheat-Fallow-T. Aman was the 3rd dominant pattern and practiced in 4.34% of the NCA in 14 upazilas. The data also revealed that the wheat based patterns stands for 14.7% of NCA. Mustard-Boro-T. Aman was the 4th dominant cropping pattern. A total of 172 cropping patterns were recognized in this region and the maximum (36) numbers of cropping patterns were identified in Paba upazila nearly followed by Durgapur (35) and Chapainawabganj upazila (34) while the lower numbers of cropping patterns were identified in Charghat (11) followed by Bagha (12) upazila of Rajshahi district. The range of cropping intensity values was recorded 171−253%. The maximum value was for Badalgachhi of Naogaon district and minimum for Bagha of Rajshahi district. The overall CDI of Rajshahi region was calculated 0.970 and the average cropping intensity at regional level was 218%. Bangladesh Rice j. 2017, 21(2): 237-254